Analisis Pengaruh Penambahan Magnesium Oksida terhadap Sifat Mekanis Bioadhesif Berbasis Kitosan-Karagenan - Amanda, Monica Putri; Budhijanto; Ramadhani, Gilang Afif Setya (Jurnal Teknik Kimia USU, 2024)
This study investigates the effect of magnesium oxide (MgO) as a filler in enhancing the bioadhesive properties of chitosan and carrageenan-based adhesives. The primary focus is on improving tensile strength, viscosity, solid content, and thermal properties. The results indicate that the addition of 0.75% w/v MgO significantly increased tensile strength from 9.76 kPa to 21.76 kPa and viscosity from 34.26 cP to 617 cP with a 0.5% w/v MgO addition. The solid content also increased from 9.81% to 13.19% with increased MgO concentration. The addition of benzoyl peroxide (BPO) reduced curing time, enhancing process efficiency. Scanning Electron Microscopy and Fourier Transform Infrared Spectroscopy confirmed improvements in structural and chemical stability, while Differential Scanning Calorimetry showed better curing efficiency. This study suggests MgO as a potential filler to improve mechanical properties and adhesion of bioadhesives, relevant for medical applications.